Quantitative capillary supercritical fluid chromatography and supercritical fluid extraction of basic drugs of abuse - Edder, Patrick; Haerdi, Werner; Veuthey, Jean-Luc; Staub, Christian
Chimia. 46(4): 141-148; 1992